2015
DOI: 10.1007/s11605-015-2897-x
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Subgroup Treatable for Laparoscopic and Endoscopic Cooperative Surgery in Undifferentiated Early Gastric Cancer: the Role of Lymph Node Metastasis

Abstract: ESD alone may be a sufficient treatment for intramucosal undifferentiated EGC if the tumor is less than 2.0 cm in size and when LVI is absent upon postoperative histological examination. LECS is feasible and safe for patients with undifferentiated EGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Signet ring cell carcinoma is not more likely than differentiated carcinoma to develop LNM when it is confined to the mucosa and is <2 cm. This observation is consistent with research by Li et al [18] However, it remains to be confirmed with a larger sample size and follow-up data. It also remains controversial whether ESD can be performed on undifferentiated cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Signet ring cell carcinoma is not more likely than differentiated carcinoma to develop LNM when it is confined to the mucosa and is <2 cm. This observation is consistent with research by Li et al [18] However, it remains to be confirmed with a larger sample size and follow-up data. It also remains controversial whether ESD can be performed on undifferentiated cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Other techniques (Table 3 ) have been developed to avoid spread of the tumor to the peritoneum[ 37 - 39 ]. When performed by expert teams they show a lot of promise and achieve solid oncologic results[ 40 , 41 ]. Use and standardization of these minimally invasive surgical procedures contributes to reduction of unnecessary gastrectomy for gastric submucosal tumors[ 42 ].…”
Section: Treatmentmentioning
confidence: 99%
“…This may minimize postoperative complications and improve quality of life, without impairment of prognosis. [26][27][28][29] In this study, it is not surprising that older patients appear in the "Additional surgery" group, given the less invasive nature of endoscopic procedures.…”
Section: Discussionmentioning
confidence: 75%
“…This study provides indirect evidence for the possibility of minimally invasive and organ‐preserving surgery, including sentinel node navigation surgery (SNNS) in EGC of noncurative ER. This may minimize postoperative complications and improve quality of life, without impairment of prognosis . In this study, it is not surprising that older patients appear in the “Additional surgery” group, given the less invasive nature of endoscopic procedures.…”
Section: Discussionmentioning
confidence: 82%